Case report: Shingles-associated probable Bickerstaff brainstem encephalitis with IgM anti-sulfatide positivity - Fu, Xiaoxue; Zhan, Qianli; Zhang, Linjie; Tian, Xiaoyan (Frontiers in Immunology, 2024)
Background Bickerstaff brainstem encephalitis (BBE) is a rare disease considered caused by acute demyelination of the brainstem, most often resulting from secondary autoimmune responses. To our knowledge, this is the first probable case report of shingles-associated BBE with anti-sulfatide IgM positivity. Case presentation We report the case of an 83-year-old woman with symptoms of progressive limb weakness, difficulty swallowing food, and disturbed consciousness that occurred 4 weeks following herpes zoster infection. Autoimmune anti-sulfatide antibodies were positive and fluid-attenuated inversion recovery (FLAIR) sequences revealed clear high signal intensity in pons and bilateral thalamus. Our patient’s condition improved markedly with glucocorticoid treatment. After 2 months of treatment, our patient was fully recovered. We considered that for her case, BBE is the most appropriate diagnosis. Conclusions We emphasize the importance of a careful medical history and assessment of clinical symptoms, performing MRI, testing autoimmune antibodies for rapid diagnosis, and ruling out differential diagnoses. Further studies involving more patients with BBE with IgM anti-sulfatide autoantibodies will increase the understanding of the clinical characteristics and advance the diagnosis and treatment of this syndrome. Meanwhile, it is crucial for dermatologists to know about this severe neurological complication following shingles.